Understanding Affective Evaluation in Retail: Consumers Perspective [Entendiendo la Evaluación Afectiva en Retail: Perspectiva de Los Consumidores] - Marinao-Artigas, E (Emerald Group Holdings Ltd., 2019)
Purpose: The purpose of this paper is to analyze the effect of the consumer’s emotional shopping experience on the perception of benefits and on the corporate reputation of a department store. Design/methodology/approach: This study was applied to a non-probabilistic sample survey proportionally distributed among the main department stores in Chile and Mexico. Findings: The findings show for both countries that the functional and symbolic benefit perceived by consumers significantly influences the reputation of department stores. However, the hedonic benefit perceived by the consumer had a negative effect on the reputation of the store. Practical implications: The companies could redirect their marketing and commercial management strategies based on the variables and relationships of the model proposed in this study. For instance, managers should implement strategies to improve the emotional experience of their clients. In addition, future studies also could use other variables inherent to the consumer’s purchasing behavior to evaluate their effects on the corporate reputation of the department store. Originality/value: This research contributes with the proposal of an explanatory model for decision making, using structural equations that suggest that the affective evaluation of the shopping experience is a key antecedent of the functional, hedonic and symbolic benefits perceived by the consumer. Moreover, the emotional experience plays a key role as an antecedent for the corporate reputation of a company. © 2019, Emerald Publishing Limited.